Exploring communication patterns among international students in Indonesia: a study using communication accommodation theory - Fariha Bibi; Layli Hamida (Cogent Arts & Humanities)
Despite a significant influx of Asian students to Indonesia, little research addresses their cultural adjustment. This study investigates communication patterns among 30 postgraduate international students at Airlangga University, Indonesia, using an ethnographic approach and communication accommodation theory (CAT). Through participant observation, interviews and inductive thematic analysis, the research explores how international students adapt their communication patterns, strategies and behaviors in the Indonesian cultural context. This study investigates the role of accommodation and convergence in cross-cultural interactions, shedding light on communication dynamics among international students and their Indonesian counterparts. Findings reveal diverse experiences; while 50% adapt well to cultural diversity, over half actively converge with Indonesian norms. Language poses a substantial hurdle, with 70% facing challenges in daily communication. The study sheds light on accommodation and convergence dynamics in cross-cultural interactions, emphasizing the impact on communication among international students and Indonesians. This research enhances understanding of intercultural communication, offering valuable insights for educators, policymakers and institutions supporting international students.